Efficacy of ozone adjuvant therapy in COVID-19 patients: A meta-analysis study - Jafari-Oori, Mehdi; Vahedian-azimi, Amir; Ghorbanzadeh, Kobra; Sepahvand, Elham; Dehi, Manijeh; Ebadi, Abbas; Izadi, Mortaza (Frontiers in Medicine, 2022)
Introduction Using ozone therapy to manage COVID-19 patients has been accompanied by conflicting results in prior studies. Therefore, we aimed to widely assess the effects of ozone as adjuvant therapy in COVID-19 patients. Methods PubMed, Scopus, Web of Science, Cochrane, ProQuest, Springer, and Sage journals were searched systematically until April 2022. Mortality rate, ICU admission, hospital-length stay, negative PCR, pulmonary, renal, and hepatic functions, as well as inflammatory and blood systems were pooled to compare the efficacy of ozone as adjacent therapy (OZ) and standard treatment (ST). Analyses were run with the random/fixed models, sub-group analysis, funnel plot, and sensitivity analysis using comprehensive meta-analysis (CMA) software version 2.0. Results The results of four randomized clinical trials (RCTs) and four case-control studies with a total of 371 COVID-19 positive patients were analyzed. The OZ group patients had a shorter length of hospital stay (P > 0.05), lower ICU admissions (P > 0.05), and lower mortality rates (P < 0.05) than the ST group cases. After treatment, 41% more COVID-19 patients had negative PCR tests than the ST group (P < 0.05). Serum creatinine and urea levels were not modified in either group (P > 0.05). Moreover, except for albumin serum levels, which decreased significantly in the OZ group, serum bilirubin, ALT, and AST were not modified in either group (P > 0.05). Both arms did not show a decrease in C-reactive protein blood levels (P > 0.05), but the OZ group showed a significant modification in LDH serum levels (P < 0.05). Unlike the d-dimer and WBC serum levels (P > 0.05), platelet levels were increased in the OZ group (P < 0.05). No negative side effects were demonstrated in either group. Conclusion Ozone therapy was effective significantly on PCR test and LDH serum levels, as well as mortality based on overall estimation. Concerning the length of hospital stay and ICU admissions, although the results were insignificant, their effect sizes were notable clinically. More RCT studies are needed to show the efficacy of ozone therapy on other studied variables.